Prognostic impact of postoperative fixed‐point inflammation in patients with gastric cancer after curative gastrectomy: A validation cohort study - Ryota Matsui; Manabu Ohashi; Motonari Ri; Rie Makuuchi; Tomoyuki Irino; Masaru Hayami; Takeshi Sano; Souya Nunobe (Annals of Gastroenterological Surgery)
Abstract Background This study aimed to determine the cutoff values of C‐reactive protein (CRP) on postoperative day 3 to predict poor overall survival (OS) in men and women with gastric cancer after radical gastrectomy. Methods This retrospective cohort study included consecutive patients who underwent radical gastrectomy for primary pStages I–III gastric cancer between May 2006 and March 2017. The patients were randomly divided 6:4 into a training set, which examined the cutoff values for CRP, and a validation set, which validated the cutoff values. Patients with a CRP level higher than the cutoff value were defined as the high‐CRP group, and those with a CRP level lower than the cutoff value were defined as the low‐CRP group. We compared the OS of the high and low CRP groups using the log‐rank test and identified prognostic factors using Cox proportional hazards regression analysis. Results We examined the cutoff values of CRP, which were 19.1 mg/dL for men and 8.1 mg/dL for women. The median follow‐up duration was 66 months. The high‐CRP group had poorer OS than the low‐CRP group (p < 0.001). Multivariate analyses showed that a high CRP level was an independent poor prognostic factor for OS in all patients (hazard ratio, 1.356; 95% confidence interval, 1.168–1.576; p < 0.001), not only in patients without postoperative complications (p = 0.001) but also in patients with postoperative complications (p = 0.023). Conclusion This study demonstrated that a high postoperative CRP was an independent poor prognostic factor for OS in patients with gastric cancer after radical gastrectomy.